Analisis Yuridis Pasal 26 Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi terhadap Kebocoran Data Digital di Indonesia - Sri Andrian; Arief Fahmi Lubis; Abdul Kholiq; Tiwuk Herawati; Istiarsyah Istiarsyah (Eastasouth Institute, 2026)
This study examines Article 26 of Law No. 27 of 2022 on Personal Data Protection (PDP Law) in Indonesia, focusing on its provisions related to digital data breaches. With the increasing use of digital platforms, the risk of personal data breaches has grown significantly, making data protection a critical issue for policymakers. Article 26 outlines the obligations of data controllers and processors in the event of a data breach, particularly requiring prompt notification to affected individuals and the relevant regulatory authority. This paper employs a normative legal analysis to assess the effectiveness of these provisions in safeguarding personal data, comparing them with international standards such as the European Union’s General Data Protection Regulation (GDPR). The analysis identifies strengths, including the obligation to notify breaches, while also highlighting weaknesses, such as the absence of clear deadlines for breach reporting and insufficient enforcement mechanisms. The study concludes with recommendations to strengthen the Personal Data Protection Law, including clarifying notification timelines, enhancing sanctions, and improving infrastructure for breach reporting and law enforcement.